(untitled) (Archive of Conferences, 2021)
This article reveals cultural law and scientific-theoretical bases of equality in the family. Family as a social institute is a fully micro-social system which gives opportunity to make collaboration, to gather requirements and also demands, to get command property and interests, and make relationship among the people. Particularly in the family human recognize the value of himself, meaning of this life and good manners.